Thermal Adaptation and Comfort Zones in Urban Semi-Outdoor Environments - Nakano, Junta; Tanabe, Shin-ichi (Frontiers in Built Environment, 2020)
Thermal adaptation characteristics and thermal comfort zone were investigated in urban semi-outdoor environment by seasonal field measurements. Four urban spaces with different levels of environmental control were selected in Tokyo, Japan. Occupants in urban semi-outdoor environment were adjusting themselves within a certain range of SET* under various environmental conditions. MRT and air velocity of the occupied environment were not necessarily selected to satisfy thermal comfort. Clothing adjustments showed higher correlation with outdoor temperature, not the immediate environment. Occupants in non-HVAC spaces were more responsive to their environment and chose not to stay when the surrounding temperature became lower. The comfort zone in SET* was found to be 19 - 30°C for HVAC spaces and 15 - 32°C for non-HVAC spaces. Occupants in semi-outdoor environment were tolerant of thermal environment 2 to 3 times wider in range than the PPD prediction. Maximum number of occupants was confirmed at 24 °C in SET* when the perceived thermal environment was evaluated to be most comfortable.